Concurrent PEDF deficiency and Kras mutation induce invasive pancreatic cancer and adipose-rich stroma in mice - Grippo, Paul J.; Adrian, Kevin; Flesche, Jan B. (Gut, 2012)
Background and aims Pigment epithelium-derived factor (PEDF), a non-inhibitory SERPIN with potent antiangiogenic activity, has been recently implicated in metabolism and adipogenesis, both of which are known to influence pancreatic cancer progression. Increased pancreatic fat in human pancreatic tumour correlates with greater tumour dissemination while PEDF deficiency in mice promotes pancreatic hyperplasia and visceral obesity. Oncogenic Ras, the most common mutation in pancreatic ductal adenocarcinoma (PDAC), has similarly been shown to promote adipogenesis and premalignant lesions. Methods; In order to determine whether concurrent loss of PEDF is sufficient to promote adipogenesis and tumorigenesis in the pancreas, the authors ablated PEDF in an EL-KrasG12D mouse model of non-invasive cystic papillary neoplasms. Results: EL-KrasG12D/PEDF deficient mice developed invasive PDAC associated with enhanced matrix metalloproteinase (MMP)-2 and MMP-9 expression and increased peripancreatic fat with adipocyte hypertrophy and intrapancreatic adipocyte infiltration (pancreatic steatosis). In support of increased adipogenesis, the stroma of the pancreas of EL-KrasG12D/PEDF deficient mice demonstrated higher tissue levels of two lipid droplet associated proteins, tail-interacting protein 47 (TIP47, perilipin 3) and adipose differentiation-related protein (ADRP, Pperilipin 2), while adipose triglyceride lipase, a key factor in lipolysis, was decreased. In patients with PDAC, both tissue and serum levels of PEDF were decreased, stromal TIP47 expression was higher and the tissue VEGF to PEDF ratio was increased (p<0.05). Conclusions: These data highlight the importance of lipid metabolism in the tumour microenvironment and identify PEDF as a critical negative regulator of both adiposity and tumour invasion in the pancreas.